Original paperInsulin growth factor-1 and insulin growth factor binding protein-3 in Egyptian patients with chronic hepatitis C - Raslan, Hala Mohamed; Ezzat, Wafaa Mohamed; Ahmed, Mohamed Mahmoud; Rasheed, Enas Abdel (Archives of Medical Science, 2007)
Introduction: The liver is the major source of insulin growth factor-1 (IGF-1) and its main binding protein, insulin growth factor binding protein-3 (IGFBP-3), which modify its bioavailability, and their concentrations might reflect liver synthetic capacity. The aim of the study was to evaluate serum levels of IGF-1 and IGFBP-3 in patients with chronic hepatitis C and their potential use as a marker of hepatic synthetic capacity. Material and methods: Thirty patients with chronic hepatitis C virus infection were included in the study: 16 patients with chronic hepatitis and 14 patients with liver cirrhosis. Thirteen healthy volunteers, age and sex matched with the cases, were used as a control group. Serum IGF-1 and IGFBP-3 were measured in all patients and controls by enzyme-linked immunosorbent assay (ELISA). Results: Serum levels of IGF-1 in patients with liver cirrhosis were significantly lower than those in patients with chronic hepatitis and those in healthy controls (110.4±57 ng/ml, 308.1±188.5 ng/ml and 274.1±81.6 ng/ml respectively, p<0.001). IGF-1 correlated negatively with age and AST (r=-0.467 and -0.393 respectively, p £0.05), and positively with prothrombin concentration (r=0.461, p=0.05). Serum levels of IGFBP-3 were significantly lower in patients with chronic hepatitis and liver cirrhosis than those in healthy controls (3576.8±743.5 ng/ml, 2323.1±1073.1 ng/ml and 4675.1±1274.2 ng/ml respectively, p<0.001) with a significant difference between patients with liver cirrhosis and patients with chronic hepatitis (p<0.001). Also IGFBP-3 was significantly lower in patients with schistosoma infection than in patients without schistosoma (2648.3±838.1 ng/ml and 4058±1513.4 ng/ml respectively, p=0.002). IGFPP-3 correlated negatively with age and AST (r=-0.485 and -0.619 respectively, p<0.001) and positively with serum albumin and prothrombin concentration (r=0.509 and 0.617 respectively, p=0.02 and 0.006 respectively). Conclusions: IGF-1 and IGFBP-3 may be useful parameters for assessment of liver function. IGFBP-3 is an early predictor of hepatic dysfunction and can be used as a marker for the severity of liver disease.